An automated room disinfection system using ozone is highly active against surrogates for SARS-CoV-2. (June 2021) - Franke, G.; Knobling, B.; Brill, F.H.; Becker, B.; Klupp, E.M.; Belmar Campos, C.; Pfefferle, S.; Lütgehetmann, M.; Knobloch, J.K.
Summary: Background: The presence of coronaviruses on surfaces in the patient environment is a potential source of indirect transmission. Manual cleaning and disinfection measures do not always achieve sufficient removal of surface contamination. This increases the importance of automated solutions in the context of final disinfection of rooms in the hospital setting. Ozone is a highly effective disinfectant which, combined with high humidity, is an effective agent against respiratory viruses. Current devices allow continuous nebulization for high room humidity as well as ozone production without any consumables. Aim: In the following study, the effectiveness of a fully automatic room decontamination system based on ozone was tested against bacteriophage Φ6 (phi 6) and bovine coronavirus L9, as surrogate viruses for the pandemic coronavirus SARS-CoV-2. Methods: For this purpose, various surfaces (ceramic tile, stainless steel surface and furniture board) were soiled with the surrogate viruses and placed at two different levels in a gas-tight test room. After using the automatic decontamination device according to the manufacturer's instructions, the surrogate viruses were recovered from the surfaces and examined by quantitative cultures. Then, reduction factors were calculated. Findings: The ozone-based room decontamination device achieved virucidal efficacy (reduction factor >4 log10 ) against both surrogate organisms regardless of the different surfaces and positions confirming a high activity under the used conditions. Conclusion: Ozone is highly active against SARS-CoV-2 surrogate organisms. Further investigations are necessary for a safe application and efficacy in practice as well as integration into routine processes.